Perbandingan Pengaruh Terapi Musik Religin dengan Kompes Hangat terhadap Intensitas Nyeri Persalinan Kala I Fase Aktif - Yessy Arisman; Via Wiyana; Siti Sundari (Jurnal Bidan Mandiri, 2024)
Uterine contractions, emotional stress, cervical dilatation and uterine muscle hypoxia are some of the causes of labor pain. Pain that is felt continuously when there are contractions can have a pathological impact which results in fatigue so that uterine contractions decrease and prolonged labor can occur, this can also endanger the mother and fetus. Handling this problem in a non-pharmacological way needs to be developed, for example by using religious music therapy and warm compresses. The purpose of this study was to compare the effect of religious music therapy and warm compresses on mothers in the first active phase of labor at the Juliana Tanjung Morawa clinic. This study used a quasy experimental research design by designing two pretest-posttest groups with 20 samples which were then divided into 2 groups. namely 10 samples for the group giving religious music therapy and 10 samples for giving warm compresses. The findings demonstrated that the mean level of labor pain during the initial active phase of the active phase in the religious music therapy group was 13.00 and the average pain intensity in the first active phase of labor in the warm compress group was 8.00 and the outcomes of the statistical test that was conducted p-value 0.028 <0.05 means that there is a comparison of the effect of religious music therapy with warm compresses on the intensity of active phase I labor pain at the Juliana Tanjung Morawa Clinic with an average difference of 5.00.